Análise teórica de vigas de concreto armado reforçadas à flexão com mantas de PRFC - Nobre, Sariny Stefany Silva (Universidade Federal Rural do Semi-Árido, 2017)
Pathologies are phenomena that appear in structures causing loss of resistance of reinforced concrete materials. Sometimes, it is necessary to apply methods that solve situations of possible rupture of the elements due to these pathologies. Various methods are applied to the construction market, where one of these is the application of the reinforcement with the use of carbon fiber reinforced polymer (PRFC). This material has been used due to its high resistant capacity, being able to lengthen absorbing the loadings of the structure. It is possible to determine the area of reinforcement required for each requesting moment in the structures, after the actual need for such use has been completed. In this work, the flexural dimensioning method will be demonstrated, focusing also briefly on the issues involved in shear. It was determined the strength of sections used by Ferrari (et al, 2002), using two beams for possible comparison between resistant moments with and without the presence of reinforcement. Following, the cracking and actuation moments of these beams were determined and a comparative analysis was made with the data obtained by the Ferrarri (et al, 2002) tests.
Keywords: Reforço; Flexão; Fibra de carbono; Vigas; Reinforcement.; Flexion; Carbon fiber; Beams; ENGENHARIAS::ENGENHARIA CIVIL